Novel Phenazine 5, 10-Dioxides Release OH in Simulated Hypoxia and Induce Reduction of Tumour Volume In Vivo. (22nd June 2011) - Lavaggi, María L.; Cabrera, Mauricio; Pintos, Cristina; Arredondo, Carolina; Pachón, Gisela; Rodríguez, Jorge; Raymondo, Stella; Pacheco, José Pedro; Cascante, Marta; Olea-Azar, Claudio; López de Ceráin, Adela; Monge, Antonio; et al.
Abstract : Phenazine 5, 10-dioxides (PDOs) are a new class of bioreductive cytotoxins, which could act towards tumours containing hypoxic regions. The PDOs selective-hypoxic bioreduction was probed in vitro ; however, the mechanism of action has not been completely explained. Besides, PDOs in vivo antitumour activities have not been demonstrated hitherto. We study the mechanism of hypoxic/normoxic cytotoxicity of PDO representative members. Electron spin resonance is used to confirm OH production, alkaline comet assay to determine genotoxicity, and gel electrophoresis and flow cytometry to analyze DNA fragmentation and cell cycle distribution. Chemically induced rat breast tumours are employed to evaluate in vivo activities. For the most selective cytotoxin, 7(8)-bromo-2-hydroxyphenazine 5, 10-dioxide (PDO1), exclusive hypoxic OH production is evidenced, while for the unselective ones, OH is produced in both conditions (normoxia and simulated hypoxia). In normoxia (Caco-2 cells), PDO1 induces cell-cycle arrest and DNA fragmentation but does not significantly induce apoptosis neither at IC50 nor IC80 . No difference in the comet-assay scores are observed in normoxia and simulated hypoxia being the unselective 2-amino-7(8)-bromophenazine 5, 10-dioxide (PDO2) the most genotoxic. The in vivo efficacy with the absence of systemic toxicity of PDO1 and PDO2 is checked out. Results from this study highlight the potential of PDOs as new therapeutics for cancer.